Reconciliation and Coming Together in DeLillo’s Falling Man - Dhobi, Saleem (Patan Prospective Journal, 2022)
This article underpins the possibility of coming together in the aftermath of 9/11 as depicted in Don DeLillo’s Falling Man. The reconciliation between the minorities and the mainstream Americans can be possible in case conflicting groups move ahead for negotiation by accepting cultural differences that became the cause of the contemporary problems in the American society in the immediate future of the 9/11 attacks. The paper has explored that there is a huge possibility of reconciliation among diverse communities when the liberal Americans take initiatives as portrayed in the novel. The obstacles to the move for negotiation are fundamentalist Muslims and orthodox Americans who intensify conflict for their vested interests. The paper has employed qualitative research design to analyze the narrative and has also looked into the issue from the multicultural perspective that respects differences. Unity in diversity and strength in togetherness is the finding of the paper. Characters like Amir in the novel are Muslim fundamentalists and characters like Martin and Nina are liberals who seek for reunion among American communities as represented by Keith and Lianne.